Media and the sexualization of childhood - Gunter, Barrie (London Routledge, 2014)
"Media and the Sexualization of Childhood examines the on-going debates surrounding the prominence of sexual themes in children's lives, from clothes and accessories, toys and games, to music, entertainment media, advertising, and new media platforms. Parents, educators and politicians around the developed world have raised concerns about the effects all these experiences can have on the socialisation and psychological development of children and the extent to which the premature introduction of sexuality into their lives can place them at risk of unwanted attention. This book explores these issues using an evidence based approach that draws on research findings from around the world, representing the most comprehensive single account of the field. The book will be invaluable to students studying topics surrounding children and the media and childhood studies, as well as students of communication, media, cultural studies, sociology, psychology and health science"--Publisher.
Includes bibliographical references and index.
Keywords: Mass media and children; Sex in mass media; Children and sex; Children -- Sexual behavior; Mass media -- Influence